The Evaluating Skin Acid–Base Balance After Application of Cold-Processed and Hot-Processed Natural Soaps: A Double-Blind pH Monitoring Study - Julita Zdrada-Nowak; Sandra Aniołkowska; Małgorzata Deska (Cosmetics, 2025)
Maintaining the physiological acid–base balance of the skin is critical to preserving the integrity of the epidermal barrier and preventing irritation. This study investigates the short-term effects of natural soaps, prepared using cold and hot processes, on skin surface pH. A double-blind, controlled design was applied to assess changes in pH following application of soap formulations. pH levels were measured in vivo using non-invasive instrumentation at baseline and 2, 15 and 30 min post-application in 41 adult volunteers. The results demonstrated a significant increase in skin pH immediately after exposure to both types of natural soap, with elevated values persisting for up to 30 min. These changes were associated with potential disruption of the skin’s acid mantle and reduced buffering capacity. The findings highlight the importance of pH considerations in the formulation and routine use of natural cleansers. Although natural soaps are often perceived as gentle alternatives, their alkalinity may transiently disturb the skin’s acid–base homeostasis, potentially leading to increased transepidermal water loss and barrier impairment. This study supports the need for reformulation strategies and consumer awareness regarding the physicochemical impact of cleansing agents on skin health.